The influence of Nusselt number on dropwise condensation heat transfer for a single droplet on inclined and grooved surfaces - Loghman Mohammadpour; Hesam Moghadasi; Ali Moosavi (Scientific Reports)
Abstract Dropwise condensation (DWC) is a widely studied vapor–liquid phase-change process that has attracted significant research attention due to its exceptional energy transfer efficiency. Therefore, it is highly important to predict the heat transfer rate during DWC and the factors that affect it. This study presents a computational fluid dynamics (CFD) investigation on DWC heat transfer under diverse circumstances for a single droplet on inclined and rough surfaces with Wenzel structure. Drop’s shape simulation was done utilizing the Surface Evolver (SE) software and the governing equations were solved based on the finite volume method. Moreover, for different Nusselt numbers ( $$Nu$$ ), the average heat flux was calculated by considering the effect of different inclination angles, contact angles, and saturation temperatures. Validation was performed by comparing the outcomes with the available data in the literature, and a satisfactory agreement was achieved. The study revealed that the average heat flux for a water droplet with the saturation temperature $${T}_{sat}$$ = 313 K on an inclined surface with an inclination angle of β  =  90° increases by 151.79% when the Nu is increased from 510 to 740. Similarly, for a droplet on a rough surface with a roughness index of $${r}_{i}$$ = 0.6, the increase in heat flux is 152%. Moreover, an increase in saturation temperature results in a higher heat flux for both inclined and rough surfaces. The augmentation follows a specific trend for each of the surfaces.